A simplified model of a damaged, vibrating structural element based on the strain energy method - Laura, Patricio Adolfo Antonio (2000)
An extension of the previously developed damage-detection algorithm for plate-like structures characterized by two-dimensional curvature is given. The fundamental frequency coefficient of the damaged structural element is obtained as a function of the intervening physical and geometric parameters Dr/D:Dθ/Dr, μ, μ-θ and b/a by means of the optimized Rayleigh-Ritz method.